Quantitative comparison between type Ia supernova spectra at low and high redshifts: a case study - Garavini, G; Folatelli, G; Nobili, S; Aldering, G; Amanullah, R; Antilogus, P; Astier, P; Blanc, G; Bronder, T; Burns, MS; Conley, A; Deustua, SE; et al. (2007)
We develop a method to measure the strength of the absorption features in type la supernova (SN la) spectra and use it to make a quantitative comparisons between the spectra of type la supernovae at low and high redshifts. In this case study, we apply the method to 12 high-redshift (0.212 ≤ z ≤ 0.912) SNe la observed by the Supernova Cosmology Project. Through measurements of the strengths of these features and of the blueshift of the absorption minimum in Ca II HandK, we show that the spectra of the high-redshift SNe Ia are quantitatively similar to spectra of nearby SNe la (z < 0.15). One supernova in our high redshift sample, SN 2002fd at z = 0.279, is found to have spectral characteristics that are associated with peculiar SN 1991T/SN 1999aa-like supernovae. © ESO 2007.